Pengaruh Nilai Pelanggan dan Customer Relationship Marketing terhadap Kepuasan Pelanggan serta Implikasinya pada Loyalitas Pelanggan - Kadir Kadir; Deni Mochamad Ramdani (Kontigensi : Jurnal Ilmiah Manajemen, 2017)
The aims of this study to determine the impact of customer value and customer relationship marketing to customer satisfaction and its implications on customer loyalty. The research method used is descriptive verification method. The population is business customers of PT. Deanstey Modish Raya Bandung with the surveyed sample was 112 respondents. Survey mamanfaatkan google form for the deployment and filling questionnaire. The analysis technique used is path analysis. The result of the research shows that the respondents think that customer value variable, customer relationship marketing, customer satisfaction, customer loyalty are in good category, but many indicators are still not optimal. The influence of customer value on customer satisfaction is 32.3% positive and significant, the influence of customer relationship marketing to customer satisfaction is 13.7% positive and significant, the influence of customer value and customer relationship marketing to customer satisfaction simultaneously is 82.2% positive significant and the remaining 17.8% is influenced by anything else beyond this research. The last influence of customer satisfaction on customer loyalty is 84% positive significant and the remaining 16% influenced by other things outside this research.